Minimally Invasive Management of Civilian Gunshot Wounds to the Lumbar Spine: A Case Series and Technical Report. Issue 3 (6th March 2020) - Crutcher, Clifford L; Wilson, John M; DiGiorgio, Anthony M; Fannin, Erin S; Shields, Jessica A; Morrow, Kevin D; Tender, Gabriel C
Abstract: BACKGROUND: Treatment of penetrating gunshot wounds (GSW) to the spine remains controversial. The decision to operate is often based on surgeon preference and experience. We present a case series of 7 patients who underwent minimally invasive thoracolumbar/sacral decompression and bullet removal at a level 1 trauma center. OBJECTIVE: To describe the use of minimally invasive techniques to achieve decompression and bullet removal for GSW to the spine. METHODS: From 2010 to 2017, 7 patients with spinal GSW underwent minimally invasive decompression and bullet removal at an academic level 1 trauma center. RESULTS: Patient ages ranged from 20 to 55 yr (mean: 31 yr). The mechanisms of injury were GSW to the abdomen/pelvis (n = 6) and direct GSW to the spine (n = 1). Based on the neurological examination, the injuries were characterized as complete (n = 1) or incomplete (n = 6). Decompression and bullet removal were performed using a tubular retractor system. All patients with incomplete injuries who had postdischarge follow-up demonstrated some neurologic recovery. There were no postoperative wound infections, cerebrospinal fluid (CSF) fistulas, or other complications related to the procedure. CONCLUSION: Minimally invasive decompression and bullet removal is a safe technique that may help reduce the risk of postoperative infections and CSF fistulas in patients with GSW to the lumbar spine compared to the standard open technique. This approach appears to be particularly beneficial in patients with incomplete injuries and neuropathic pain refractory to medical treatment.